Cost-Effectiveness of Meropenem Versus Ceftriaxone for the Treatment of Sepsis at Dr. Tadjuddin Chalid Hospital Makassar - Saud, Anshar; Mutmainnah, Alfira; Arifin, Bustanul (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Sepsis is a critical condition arising from the body's response to an infection. In Indonesia, the incidence of sepsis remains notably high, with mortality rates reaching 49%. At Dr. Tadjuddin Chalid Hospital Makassar, meropenem and ceftriaxone are extensively utilized as empirical therapies. Conducting a cost-effectiveness analysis is essential for ensuring rational and efficient decision-making in the selection of appropriate antibiotic therapy. This study aimed to compare the cost-effectiveness of meropenem versus ceftriaxone in treating patients with sepsis in the inpatient ward of Dr. Tadjuddin Chalid Hospital Makassar. A retrospective cross-sectional design was employed, utilizing the medical records of patients with sepsis. Data were analyzed using the Average Cost-Effectiveness Ratio (ACER) and Incremental Cost-Effectiveness Ratio (ICER) to ascertain the economic value of both antibiotics. The results indicated that the ACER value of meropenem was IDR 731,180.68, which was lower than that of ceftriaxone (IDR 775,021.41), suggesting that meropenem was more cost-effective. The incremental cost of IDR 667,206 indicates the additional expenditure required for meropenem to achieve a 1% increase in the proportion of patients with a length of stay of less than 17.4 days. The sensitivity analysis results align with the ICER analysis, which identified meropenem as more cost-effective, enabling robust conclusions. Treatment costs emerge as the key variable affecting the ICER, requiring primary consideration when interpreting cost-effectiveness results. In conclusion, meropenem is more cost-effective than ceftriaxone and can be recommended as an alternative antibiotic therapy for patients with sepsis from a pharmacoeconomic perspective.